INVESTIGATING EFL STUDENTS’ SPEAKING ANXIETY : A CASE STUDY AT ENGLISH DEPARTMENT OF UINSU - Nurul Aini; Yani Lubis (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
Anxiety about speaking English has received a lot of attention in recent years. The purpose of this study was to describe the factors that caused students' language anxiety and their strategies for reducing anxiety in speaking english at class. Participants in this study were 5 students’ English department in the second semester. The methods used in this study were descriptive and qualitative. Data were obtained from interviews and observations. The results show that EFL students in English Department of UIN Sumatera Utara, they feel anxiety in speaking English. Fear of speaking English is due to a number of factors, both internal and external. The first factor was the type of the task, fear of making mistakes, the role of the language teacher, self-perception and the last is the limited exposure to English. The finding of this study also revealed that there were some strategies they used to reduce anxiety. There are preparation before speaking English, positive thinking, and strategy they used was peer seeking.